2021
DOI: 10.1007/s10584-021-03178-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the full costs of floodplain buyouts

Abstract: Given projected increases in flood damages, managed retreat strategies are likely to become more widespread. Voluntary buyouts, where governments acquire flood-damaged properties and return the sites to open space, have been the primary form of federally funded retreat in the USA to date. However, little attention has been paid to the cost structure of buyout projects. Using a transaction cost framework, we analyze the costs of activities that comprise floodplain buyouts. Federal data do not distinguish transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Other costs including planning, communication, cleanup of infrastructure and decontamination are also important considerations. A systematic review of floodplain buyouts carried out in the US found that transaction costs typically make up about 80% of the total project costs, although consistent budgetary data is lacking (Curran-Groome et al, 2021). Nevertheless, even if the cost of managed retreat doubled, it is still less than estimates for Options 3 and 4 that are currently being promoted by the City of Abbotsford (City of Abbotsford, 2023) (Table 1).…”
Section: Recovery Scenario Costsmentioning
confidence: 99%
“…Other costs including planning, communication, cleanup of infrastructure and decontamination are also important considerations. A systematic review of floodplain buyouts carried out in the US found that transaction costs typically make up about 80% of the total project costs, although consistent budgetary data is lacking (Curran-Groome et al, 2021). Nevertheless, even if the cost of managed retreat doubled, it is still less than estimates for Options 3 and 4 that are currently being promoted by the City of Abbotsford (City of Abbotsford, 2023) (Table 1).…”
Section: Recovery Scenario Costsmentioning
confidence: 99%
“…Moreover, while the federal government provides 75% of the buyout funding, local tax rolls may be permanently reduced when valuable real estate is removed from the city's building stock (BenDor et al 2020). Total project costs add a further 25% over property buyout costs, which local governments must shoulder (Curran-Groome et al 2021).…”
Section: Fema Buyouts and Their Inequitable Effectsmentioning
confidence: 99%
“…The vast majority explore these factors at the state scale via localized/regional case study examples. This trend is reflected across a range of geographies, including the United States [57,58,[69][70][71][72][73][74][75][76][77][78]; South America [79,80]; Canada [81,82]; Western European countries including France, Germany, Austria, and Sweden [83][84][85][86][87][88][89][90][91][92][93]; the United Kingdom and Ireland [56,94,95]; and the South Asia and Asia-Pacific region [20,21,52,82,85,[96][97][98][99][100][101][102][103][104][105][106][107]. Almost all of these papers are concerned with understanding retreat from coastal or lowlying areas, with the exception of some o...…”
Section: (B) Governance Policy and Institutional Factorsmentioning
confidence: 99%
“…Although Phillips et al [137] note that the economic loss spans loss of tourism as well as loss of assets and residential properties, most of the returned papers on managed retreat examine compensation through a residential property loss lens. A significant proportion of reviewed papers explored the concept of 'buyout', and then, mainly from the United States geography and neoliberal perspective [70,71,111,[138][139][140][141] but also a New Zealand perspective [100]. The concept of buyout is where the state has provided compensation or compulsorily acquired vulnerable coastal land for the purposes of activating managed retreat.…”
Section: (C) Property Rights Neoliberalism and Social Justice Conside...mentioning
confidence: 99%